Barriers to overcome in the attempt of a massive intervention of PV systems connected to the network in Peru - Espinoza, Rafael (2017)
Electrical power consumption in Peru increased on average by 5.1% between 2002 and 2011, while demand increased from 2 700 MW to 4 800 MW as a consequence of the increase in GDP. On the other side, photovoltaic (PV) technologies have been used in Peru for power generation in a few thousand small solar home systems (SHS) in the last 25 years, through various rural home electrification programs. This has permitted to accumulate a large amount of experience, which would open the possibility to consider the installation of larger PV systems with connection to the grid. Likewise, in the last five years, power generating plants have been installed to inject power directly in the National Power Grid (SEIN, from its Spanish acronym) without any substantial intervention of the national engineering community. One can see that in this scenario of technological evolution, PV technologies is present at both extremes of the power generation scale going from Watt to MegaWatt, without any intermediary power in the KiloWatt range. In this context, the present work proposes the creation of technical backstopping and minimal conditions necessary to promote and consolidate a massive introduction of medium‐size PV facilities (100 kW ‐ 1 MW), in order to aim for a distributed power generation in Peru in the medium term of the next five years. This project is based on the analysis of the following points: a) The evolution of power generation in Peru between 1995 and 2015, considering the geographical peculiarities and with special emphasis on residential, commercial and industrial consumer profiles; b) The growth dynamics of the PV sector, which has resulted in 96 MW and 2 MW of connected and isolated power generation, respectively; c) The evolution of the import market of PV modules during the last ten years, and especially during the last three years, which has maintained a sustained growth of 2.5 MW/year; and d) Education programs for the training of technicians and engineers. The present work has counted with the technical support of a professional team from Universidad de Jaen (Spain) and Universidad Nacional de Ingeniería (Perú).